Urgensi Pendidikan Karakter dalam Upaya Penanggulangan Kenakalan Remaja - Ahdar, Ahdar; Musyarif, Musyarif (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2022)
This study discusses the causes of juvenile delinquency and the role of character education in dealing with juvenile delinquency. This study aims to enrich scientific knowledge in relation to the concepts of character education for adolescent development and to find out the motives that cause character decadence for adolescents. This research is a qualitative descriptive study that examines the prevention of juvenile delinquency. The informants of this study were 58 heads of families in Liliriaja Village. Data collection techniques used are documentation, observation, and interviews. The data analysis technique used is descriptive qualitative analysis, using data percentage tabulations. The results; first, juvenile delinquency in Liliriaja Village occurs because of several factors, namely the development of science and technology which gave birth to globalization, uncontrolled association among adolescents, Islamic because of weak families, low exemplary in social life, and so on; second, Islamic education emphasizes students to always increase faith in Allah Swt., increase taqwa awareness, social awareness, intellectual awareness, individual awareness, and so on, in carrying out their duties and functions as human beings.